Development of Banjar Munduk Malang, Sedang Village as a Historical Tourism Village through MBO Museum Literacy - I Wayan Sugiartana (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
Sedang Village, Banjar Munduk, Malang, Tabanan Regency, has great potential to be developed as a historical tourism village through the existence of the MBO Museum (Oemoem Headquarters). This museum preserves traces of the struggle of I Gusti Ngurah Rai and his troops, and symbolizes the role of the village community in supporting the independence revolution by providing protection and food logistics. The community service activities carried out by STISPOL Wira Bhakti Denpasar aim to increase historical literacy of the community, especially the younger generation, so that they understand the value of the struggle and local contributions to national history. The activity methods include historical education, interactive discussions, and training in managing museum narratives as tourist attractions. The results of the activities show an increase in public knowledge about the history of the struggle, a growing collective awareness to preserve local values, and the emergence of the idea of ​​​​developing a history-based tourism village. The MBO Museum not only functions as an educational center, but also became the forerunner to the establishment of Kodam IX/Udayana, thus having strategic value in Indonesian military history. This activity concludes that historical literacy and strengthening the role of the MBO Museum can be the foundation for the development of Sedang Village, Banjar Munduk, Malang, as a sustainable historical tourism destination. With the support of the community and universities, this village has the potential to become a center for historical education as well as a new source of income through cultural and struggle-based tourism.